The rediscovery of Hyptis argentea (Lamiaceae: Hyptidinae) in the Brazilian Cerrado after 70 years - Conegiro, Thaís Teixeira; Morais, Isa Lucia De; Goyá, Lionizia; Soares, Arthur De Souza; Antar, Guilherme Medeiros (Phytotaxa, 2026)
Hyptis is a predominantly Neotropical genus comprising approximately 170 species in its current circumscription. Despite recent taxonomic advances, several species remain poorly known, with some represented only by their type specimens and original descriptions. One such species is Hyptis argentea, described by Carl Epling and Mildred Mathias based on two materials collected by Amaro Macedo in 1950s from the municipality of Jataí, Goiás state, within the Cerrado domain, and never collected again since then. Here, we report the rediscovery of H. argentea based on recent fieldwork and herbarium revision and provide updated information on its morphology, ecology, distribution, and conservation status. The species was found in Caçu and Mineiros municipalities, more than 100 km from the original gatherings. Our findings underscore the continued importance of field exploration and herbarium revision for advancing the taxonomy of Hyptis and improving knowledge of the still insufficiently documented biodiversity of the Cerrado.